Homo interneticus – a challenge for modern education - WALAT, WOJCIECH (Journal of Education, Technology and Computer Science, 2023)
This paper presents the three characteristics that constitute the modern type of Internet man – homo interneticus – easily lead to the rapid development of functional illiteracy. Therefore, education faces a great challenge in the era of dominant and widely accepted functional illiteracy.